TINGKAT KECEMASAN (ANXIETY) WASIT BULUTANGKIS SEBELUM DAN SAAT MEMIMPIN PERTANDINGAN DI PROVINSI JAMBI - Muhammad Jumaidil Yudistira; Sukendro; Grafitte Decheline (PT. Hasba Edukasi Mandiri, 2025)
The PBSI Association of Jambi Province has referees from various districts across Jambi who are actively involved in officiating matches at both provincial and national levels. Through this system, badminton referees in Jambi are organized into one forum to develop their skills, achieving accomplishments through a long process. During this formation process, several influencing factors have been identified. The referees’ mental condition while officiating—whether at the amateur or professional level—often experiences issues such as nervousness, anxiety, and even loss of concentration when making decisions. Various phenomena may occur during badminton matches in Indonesia, at both amateur and professional levels, in which referees often become central figures in controversial decisions. The purpose of this study was to determine the level of anxiety experienced by badminton referees before and during officiating matches in Jambi Province. This research employed a quantitative descriptive method. The sample consisted of 25 badminton referees, comprising 20 men and 5 women. The results showed that the level of anxiety among badminton referees before and during matches in Jambi Province fell into the “very good” category for 1 respondent (4%), the “good” category for 14 respondents (56%), and the “moderate” category for 10 respondents (40%). For intrinsic indicators, 1 referee (4%) was in the “very good” category, 19 (76%) in the “good” category, and 5 (20%) in the “moderate” category. For extrinsic indicators, 8 referees (32%) were in the “good” category, 15 (60%) in the “moderate” category, and 2 (8%) in the “low” category. The conclusion of this research is that the anxiety level of badminton referees before and during officiating matches in Jambi Province is generally in the “good” category, with 56% of respondents falling into this group.